2014
DOI: 10.3168/jds.2014-8047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metal ions on growth, β-oxidation system, and thioesterase activity of Lactococcus lactis

Abstract: The effects of divalent metal ions (Ca(2+), Mg(2+), Fe(2+), and Cu(2+)) on the growth, β-oxidation system, and thioesterase activity of Lactococcus lactis were investigated. Different metal ions significantly influenced the growth of L. lactis: Ca(2+) and Fe(2+) accelerated growth, whereas Cu(2+) inhibited growth. Furthermore, Mg(2+) inhibited growth of L. lactis at a low concentration but stimulated growth of L. lactis at a high concentration. The divalent metal ions had significant effects on activity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…It is known that LAB often have fastidious nutritional requirements (Van Niel & Hahn‐Hägerdal, ), so the rich nutrients in maize meal and the metal ions in limestone might have a combined effect on promoting the growth of LAB. After calculating the concentration of the six main elements in the limestone, we found ensiling with limestone cannot increase the K and Zn content of MX‐treated silages, the level of Ca was far beyond its optimum range, and Fe has inhibitory effects on LAB at this level (Li & Ma, ). The content of Mg in the control and MM‐treated silages was, respectively, at 166 and 275 μg/g FM, but its content in the MX‐treated was 414 μg/g FM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that LAB often have fastidious nutritional requirements (Van Niel & Hahn‐Hägerdal, ), so the rich nutrients in maize meal and the metal ions in limestone might have a combined effect on promoting the growth of LAB. After calculating the concentration of the six main elements in the limestone, we found ensiling with limestone cannot increase the K and Zn content of MX‐treated silages, the level of Ca was far beyond its optimum range, and Fe has inhibitory effects on LAB at this level (Li & Ma, ). The content of Mg in the control and MM‐treated silages was, respectively, at 166 and 275 μg/g FM, but its content in the MX‐treated was 414 μg/g FM.…”
Section: Discussionmentioning
confidence: 99%
“…The content of Mg in the control and MM‐treated silages was, respectively, at 166 and 275 μg/g FM, but its content in the MX‐treated was 414 μg/g FM. Li and Ma () reported that the stimulating effect of Mg increases with the increment of its concentration from 192 to 480 μg/ml, so Mg must have played an important role in the growth of LAB during the early stage of ensiling. In addition, Mn also can increase the growth rate of LAB because it plays a role in detoxifying peroxides (Pahlow, Muck, Driehuis, Oude Elferink, & Spoelstra, ).…”
Section: Discussionmentioning
confidence: 99%
“…Yeast extract serves as the carbon, nitrogen and vitamin source needed to satisfy the growth requirements of the microorganisms. Several studies have underlined the important influence of metal ions on the growth of lactobacilli [2931]. We have also evaluated the effect of yeast extract, ammonium bi-sulphate, manganese and magnesium salts concentrations on dry cell mass production but according to results, they are necessary for growth but have no significant effect on response surface of growth.…”
Section: Resultsmentioning
confidence: 99%
“…The influences of trace elements on microorganism are various, and the effects of single trace elements and trace elements compound on microorganism are different. The aim of this study is to find the concentrations of trace elements, trace elements and their combinations suitable for the growth of Paenibacillus polymyxa (Li and Ma 2014 ; Trchounian et al 2016 ; Ropek and Para 2002 ; Gupta et al 2010 ). Under aseptic conditions, the PDB medium containing 5 mL different mass concentration of Cu 2+ , Fe 2+ , Mn 2+ , and Zn 2+ was added to each sterilized test tube (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%